قصور الانتباه البصري الانتقائي عند عسيري القراءة في سن 8-9 سنوات - سليم, آمنة; زايدة, مسعودة (University of Eloued جامعة الوادي, 2023)
الملخص تناولت هذه الدراسة موضوع مدى قصور الانتباه البصري عند عسيري القراءة في سن 8-9 سنوات دراسة مقارنة بين عسيري القراءة وقراء عاديين، كونهما يمثلان احدى المكونات الاساسية التي يبنى عليها تعليم الطفل القراءة. فهدفت هذه الدراسة الى معرفة مدى قصور الانتباه البصري عند عسيري القراءة والقراء العاديين، وتم اختيار مجموعة من تلاميذ سنة ثالثة ابتدائي بناءا على مجموعة معايير تشخيصية في القراءة وتم تصنيف هؤلاء الافراد الى مجموعتين قراء عاديين (64) وعسيري قراءة (19) وتم تصنيف الافراد بصورة اولية على اراء المعلمين ونتائج في مادة القراءة، اعتمدت هذه الدراسة على المنهج الوصفي المقارن. تم تطبيق اختبار قراءة الكلمات (المتداولة وغير المتداولة وشبه كلمات)، واختبار (الشطب) للانتباه البصري على جميع افراد عينة الدراسة للكشف على فروق المحتملة في هذه الاختبارات. أما فيما يتعلق بتقنيات الاحصائية المستخدمة فقد استخدمنا اختبار(ت) للفروق، ومعامل الارتباط (بيرسون) لنتائج الدراسة. بينت النتائج المتوصل اليها الى: - أنه يوجد فرق دال احصائيا عند مستوى 0.02 بين مجموعة القراء العاديين وضعاف القراءة في اختبار الشطب. - أما ما يخص الفرضية الثانية فتوصلت النتائج الى انه توجد علاقة ارتباطية موجبة دالة عند مستوى 0.000 بين الاداء القرائي والشطب. من خلال هذه النتائج تم استنتاج أهمية دور الانتباه البصري في تعلم القراءة بالنظر الى درجة الارتباط الدالة الموجودة بينهما، ثم تفسير ومناقشة النتائج في ضوء الدراسات السابقة. Abstract: This study dealt with the issue of the extent of visual attention deficits among dyslexics at the age of 8-9 years, a comparative study between dyslexics and ordinary readers, as they represent one of the basic components on which a child's reading education is built. This study aimed to find out the extent of visual attention deficits among dyslexic and normal readers. A group of third year primary students was chosen based on a set of diagnostic criteria in reading. These individuals were classified into two groups: normal readers (64) and dyslexic readers (19). Primary on teachers' opinions and results in the subject of reading, this study relied on the comparative descriptive approach. The test of reading words (common, non-common and semi-words), and the test (crossing out) of visual attention were applied to all members of the study sample to detect potential differences in these tests. As for the statistical techniques used, we used the (T) test for differences, and the correlation coefficient (Pearson) for the results of the study. The results reached showed: - There is a statistically significant difference at the level of 0.02 between the group of regular readers and poor readers in the cross-out test. - As for the second hypothesis, the results concluded that there is a positive correlation at the level of 0.000 between reading performance and crossing out. Through these results, the importance of the role of visual attention in learning to read was concluded in view of the degree of significant correlation between them, and then the interpretation and discussion of the results in the light of previous studies.
دراسة مقارنة مع قراء عاديين
مذكرة ماستر في علوم التربية تخصص تربية خاصة تعليم مكيف
Keywords: الإنتباه الإنتقائي، attention sélective,selective attention; عسر القراءة، Difficulté de la lecture, dyslexia; الإنتباه البصري، attention visuelle, visual attention